Type 1 autoimmune pancreatitis in Europe: clinical profile and response to treatment - Overbeek, Kasper A.; Poulsen, Jakob L.; Lanzillotta, Marco; Vinge-Holmquist, Olof; Macinga, Peter; Demirci, A. Fatih; Sindhunata, Daniko P.; Backhus, Johanna; Algül, Hana; Buijs, Jorie; Levy, Philippe; Kiriukova, Mariia; et al. (Clinical gastroenterology and hepatology, 2024)
Background & Aims - Autoimmune pancreatitis (AIP) is an immune-mediated disease of the pancreas with distinct pathophysiology and manifestations. Our aims were to characterize type 1 AIP in a large pan-European cohort and study the effectiveness of current treatment regimens. - Methods - We retrospectively analyzed adults diagnosed since 2005 with type 1 or not-otherwise-specified AIP in 42 European university hospitals. Type 1 AIP was uniformly diagnosed using specific diagnostic criteria. Patients with type 2 AIP and those who had undergone pancreatic surgery were excluded. The primary end point was complete remission, defined as the absence of clinical symptoms and resolution of the index radiologic pancreatic abnormalities attributed to AIP. - Results - We included 735 individuals with AIP (69% male; median age, 57 years; 85% White). Steroid treatment was started in 634 patients, of whom 9 (1%) were lost to follow-up. The remaining 625 had a 79% (496/625) complete, 18% (111/625) partial, and 97% (607/625) cumulative remission rate, whereas 3% (18/625) did not achieve remission. No treatment was given in 95 patients, who had a 61% complete (58/95), 19% partial (18/95), and 80% cumulative (76/95) spontaneous remission rate. Higher (≥0.4 mg/kg/day) corticosteroid doses were no more effective than lower (<0.4 mg/kg/day) doses (odds ratio, 0.428; 95% confidence interval, 0.054-3.387) and neither was a starting dose duration >2 weeks (odds ratio, 0.908; 95% confidence interval, 0.818-1.009). Elevated IgG4 levels were independently associated with a decreased chance of complete remission (odds ratio, 0.639; 95% confidence interval, 0.427-0.955). Relapse occurred in 30% of patients. Relapses within 6 months of remission induction were independent of the steroid-tapering duration, induction treatment duration, and total cumulative dose. - Conclusions - Patients with type 1 AIP and elevated IgG4 level may need closer monitoring. For remission induction, a starting dose of 0.4 mg/kg/day for 2 weeks followed by a short taper period seems effective. This study provides no evidence to support more aggressive regimens.